Calcium Deficiency in Diet Decreases the Magnesium Content in Bone and Affects Femur Physicochemical Properties in Growing Rats - Hernández-Becerra, Ezequiel; Jímenez-Mendoza, Daniel; Mutis-Gonzalez, Nathalia; Pineda-Gomez, Posidia; Rojas-Molina, Isela; Rodríguez-García, Mario E. (Biological trace element research, 2020)
This study evaluates the effect of three calcium levels in the diet (normal, moderate, and severe calcium depletion) on bone metabolism of male Wistar rats during their growth period. Bone mineral density (BMD) and femur length were determined in vivo during the growth stage using a single X-ray transmission system. The apparent calcium absorption was calculated in the rat adolescent and adulthood stages. At the end of the experiment, calcium concentrations in serum and urine were analyzed. The bones were evaluated postmortem to corroborate in vivo analyses. Microstructural properties of cortical and trabecular tissues of femurs bones were assessed using scanning electron microscopy. Bone mineral contents (Mg, Ca, P, and K) were quantified by inductively coupled plasma. Severe calcium depletion in the diets in the development stage affects the bone quality parameters such as bone mineral density and mineral content. Moreover, it was found thinner cortical and trabecular bone areas. Additionally, it was found that severe calcium depletion increased the apparent absorption of calcium as a defense mechanism, but with the decrease of the BMD peak, and the thickness of cortical bone as well as trabecular bone porosity. The severe calcium depletion increased the efficiency of apparent absorption calcium as a defense mechanism, but, even so, decreases the BMD peak as well as the thickness of cortical bone and trabecular bone porosity.